Short-term exposure to aggressive card game: releasing emotion without escalating post-game aggression - Zhang, Xuanyu; Teng, Huina; Zhu, Lixin; Qiu, Boyu (Frontiers in Psychology, 2025)
IntroductionCompetitive card games, a widespread hobby, often contain aggressive or violent elements. According to the general aggression model, such card games may increase players’ aggressive cognition, emotions, and behaviors. Therefore, this study recruited 168 participants aiming to examine the specific impacts of short-term aggressive card game exposure on post-game aggression.MethodPost-game cognition, emotions, and behaviors were assessed by spatial cueing task, positive and negative affect schedule, and maze selection task, respectively. Furthermore, the Penn emotion recognition test was employed to explore the emotional cognitive bias after short-term exhibiting aggressive behaviors in the card game.ResultsResults revealed that short-term exposure to the aggressive card game did not significantly increase aggressive cognition or behaviors. Conversely, in-game aggressive behaviors reduced negative emotions, increased positive emotions, and trended to perceive neutral emotions as happiness.DiscussionThese findings suggest that aggressive elements in card games could enhance emotional well-being without escalating postgame aggression. Future studies are needed to examine the long-term effects of aggressive card games, providing deeper insights into their development and application.